PENDUGAAN BAHAYA BENCANA BANJIR PADA SUB DAS BAYANG NAGARI AUR BEGALUNG KECAMATAN BAYANG INDONESIA (JURNAL SPASIAL, 2020)
Flood disaster is a disaster that often occurs in Indonesia. Many impacts arising from the disaster ended in damage and loss of property, property and lives. Flood disaster management must be taken seriously so that it does not have a huge impact on the community. One area that was once flooded was in the area around the Batang Bayang river flow, precisely in Nagari Aur begalung, Bayang Subdistrict, Pesisir Selatan Regency. Flood disaster that is suspected to occur due to high rainfall and land destruction in the upper river area. In addition to the above factors, the topography of the area also supports the occurrence of flooding, namely the relatively flat topography. The height of the floods that have occurred is estimated to reach a height of approximately one meter, so that community settlements are affected. Characteristics of floods that occur in the Bayang sub-watershed occur in a long time, but the shrinkage of the flood surface is very fast. The purpose of this study is to assess the estimation of flood hazard levels and the distribution of estimated levels of flood hazards in Batang Bayang. The method used is a descriptive method with direct measurement of spaciousness refers to the paimin method. The results obtained that the estimation of flood hazard levels at Batang Bayang obtained low results that are scattered at each research point.